Species composition and biodiversity of organisms in University of Technology Mara (UiTM) Kuala Pilah, Negeri Sembilan, Malaysia / Rosli Noormi... [et al.] - Noormi, Rosli; Shamsuddin, Raba’atun Adawiyah; Akmal Shukri, Amir Muhaimin; Sahabudin, Nur Syamimi Liyana; Abdul Rahman, Razia; Abdul Mutalib, Sharatul Nurhafiezah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
The knowledge of biological diversity serves new insights and opportunities for sustainable environment. However, information pertaining to the species composition and biodiversity of University of Technology MARA (UiTM) Kuala Pilah, Negeri Sembilan is scanty. Hence, this study was conducted to assess the species and diversity of organisms at UiTM Kuala Pilah. Using the quadrat sampling technique, 4 plots (labelled as A, B, C and D) with a size of 50 m 2 were established to obtain the organisms present in the study area. Twelve different plant species (Sensitive plant, White Spider Lily, Golden Trumpet, Weeds, Dandotapala, Camphor Grass, Love Grass, Evergreen Rose, Dandelion, Closed Gentian, Flatweed and Chinese Violet) were observed. Meanwhile, a total of ten species were identified as animals (toad, snail, earthworm, grasshopper, millipede, carpenter bee, moth, rhinoceros beetle, bird and gray’s leaf). However, only four species were obtained as fungi (mushroom, orange sea lichen, tree-dwelling lichen and button jelly lichen) in the entire plots. The findings of this study suggest that UiTM Kuala Pilah environments can provide baseline information as well as offers the contemporary strategies for preserving cultural and ecological diversity.